2020
DOI: 10.1002/mmce.22488
|View full text |Cite
|
Sign up to set email alerts
|

Design of printedUWBantenna withCPWandmicrostrip‐line‐fedforDCS/PCS/bluetooth/WLANwireless applications

Abstract: Spiral-shaped UWB antennas, which are differ from each other in terms of feeding structure are presented in this manuscript. CPW and microstrip line feeding are used to excite the designed antenna to obtain different performance parameters. The overall physical dimensions of proposed antennas are 27 × 27 × 1.6 mm 3. These antennas are designed on low cost FR4 glass epoxy substrate with 1.6 mm thickness and dielectric constant 4.4. Impedance bandwidth (S 11 < −10 dB) obtained for measured CPW-fed antenna is 176… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The proposed monopole antenna is compared with some of the most recently published works for biomedical applications in [ 2 , 3 , 4 , 5 , 6 , 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], as shown in Table 3 . The total performance of an antenna is determined by several factors, including fractional bandwidth, average gain, radiation efficiency, physical dimensions, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed monopole antenna is compared with some of the most recently published works for biomedical applications in [ 2 , 3 , 4 , 5 , 6 , 7 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ], as shown in Table 3 . The total performance of an antenna is determined by several factors, including fractional bandwidth, average gain, radiation efficiency, physical dimensions, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 shows that most published textile antennas are linearly polarized [ 3 , 40 , 41 , 42 , 43 , 46 , 47 ] with limited bandwidth operation. For SAR calculations, most published textile-based sensors acquire a low SAR at low transmitted power levels.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of size, bandwidth, gain, and operational frequency range, Table 2 shows the comparison results regarding the performance of the planned UHF/UWB triple-band antenna to that of the current antennas [18][19][20][29][30][31]. The results showed that the created reader antenna's uniqueness offered good impedance bandwidth and gain performance, and its applicability was demonstrated by utilizing a UHF/UWB triple-band monopole antenna incorporated into an RFID reader board.…”
Section: Comparison and Noveltymentioning
confidence: 99%
“…Group delay parameter of UWB antenna describes the signal delay while the signal propagates from transmitter to the receiver. For computing the group delay, two identical antennas have been kept apart from each other by 30 cm in two different orientations (face to face and side by side) and can be evaluated by using the following Equation 24–26 τgoodbreak=goodbreak−italicdθ()ω where θ is the signal phase (in Radian), and ω is the angular frequency (in Rad/sec).…”
Section: Parametric Analysis Of Antenna With Band Notch Characteristicsmentioning
confidence: 99%
“…Band stop and band pass filters are also designed to attain the desired notch characteristics, the equations used to compute the values of L and C for the band stop filters are 26 : L1goodbreak=Ro()fc2goodbreak−fc1πfc1.fc2,C1goodbreak=14πRo()fc2goodbreak−fc1 L2goodbreak=Ro4π()fc2goodbreak−fc1,C2goodbreak=fc2fc1πRofc1.fc2 The equations used to evaluate the L and C values of band pass filters are: L1'goodbreak=Roπ()fc2goodbreak−fc1,C1'goodbreak=fc2fc14πRofc1.fc2 L2'goodbreak=Ro()fc2goodbreak−fc14πfc1.fc2,C2'goodbreak=1πRo()fc2goodbreak−fc1 …”
Section: Parametric Analysis Of Antenna With Band Notch Characteristicsmentioning
confidence: 99%